The Importance of Intercultural Education in Teacher Training: Theoretical Insights - Chodzkienė, Loreta (Pedagogika, 2013)
The 21st century challenges to be taken by the citizens of the global knowledge-based society become mostly the task of a school when society expects schools to deal with different languages and student backgrounds, to be sensitive to culture and gender issues, to promote tolerance and social cohesion, and “teachers are identified as the main facilitators of education changes and mediators of society development processes in the alteration of educational systems”. However, there has always been a doubt whether teacher training programmes are designed well enough to educate them interculturally competent being able to transfer their knowledge and experience to the future generations? The Subject of the paper refers to the aspects of intercultural education. The research aims to highlight Prof. M. Lukšienė’s conceptual ideas on intercultural education as compared to the world scholars’ theoretical insights. In order to achieve the aim set the following objectives were stated: 1) to trace out the origin of intercultural education and prove its importance; 2) to discuss the proposed content formats and their implementation issues in intercultural education; 3) to review possibilities of intercultural education in teacher training; 4) to emphasize M. Lukšienė’s insights about intercultural education in Lithuania. Research method – comparative analysis of scientific literature and legal documents. The review of the scientific literature on the issues of intercultural education indicates that the origin of intercultural education dates back to the years of WW2 and after-war period when there was an urgent need to build authentic relationships with the people representing different cultural backgrounds. The history of intercultural education pointed out the names of such prominent figures in intercultural communication as E. T. Hall and G. W. Allport, who had noticed that the cases of miscommunication occurred due to people’s different conceptions of reality and searched for the ways of communication improvement. The necessity of intercultural education has also been indicated by the processes of globalization accelerating the development of relationships in a plethora of international, social, economic, political, academic and cultural fields. Intercultural Communicative competence has been identified as the subject of intercultural education, the development of its structural components (knowledge, skills and attitudes) have always been based on three different interrelated levels, – cognitive, emotional and behavioral. Having revised the ICC structural components (knowledge, skills, attitudes) it became evident that many scholars stress the role of attitudes in generating the rest of the ICC. The component of motivation has also been attributed to the domain of attitudes or even considered to be a substitute for it. The analysis of the knowledge component of ICC refers to at least three sub-components, such as the knowledge of one’s own culture, culture-general knowledge and culture specific knowledge. Building authentic relationships with the host country people is highly dependent on such skills as listening observing and evaluating; analysing, interpreting and relating. Also, interactants’ communication skills, that encompass their verbal and nonverbal behaviors related to message skills, behavioral flexibility, interaction management and social skills were stressed to be of utmost importance, helping to find the balance between one‘s own and others‘ interests in the contexts of different cultures. Talking about the intercultural education in the context of Lithuania, S. Šalkauskis, a prominent philosopher and educator of the inter-war period, could be considered the initiator of this education. S. Šalkauskis searched for a synthesis between East and West. Bearing in mind the geopolitical position of the country, the scholar advocated the importance of foreign languages for successful international communication and cooperation. Although there exist many interpretations of content to be included in intercultural education the majority of them focus on the development of a person‘s awareness of the fundamental cultural patterns – beliefs, values, norms and social practices – affecting perceptions of the competence. The scientists maintain the opinion that there cannot be the only one „prescriptive“ model to develop one‘s intercultural communicative competence, nevertheless, many of them agree about the five culture dimensions to be integrated into a course or study programme targeting at intercultural development. The mentioned domains are as follows: 1) Learning about the Self as a Cultural Being; 2) Learning about the Elements of Culture; 3) Culture - Specific Learning; 4) Culture-General Learning; 5) Learning about Learning. I has also to be added, that the majority of the scientists representing intercultural training schools maintain that the development of interculturally competent teachers depends upon the interdisciplinary character of training, however, some attribute this mission to foreign language teaching when studying a foreign language there is always a constant relationship between the “world of origin” and the “world of the target language“. Intercultural education in teacher training is advised to be integrated throughout the whole study programmes when an envisaged term of mobility encompasses a range of subjects and choice of teaching strategies that would shape the teacher-students‘ worldview and encourage their self - reflection. Professor M. Lukšienė’s theoretical insights about the education of a person respecting his/her own roots and open to innovations reflect the pedagogical thoughts of many world scholars at that time. The scientist‘s works encompass discussions about society, school, class environment and its characters – a teacher and a student, education content and methods to be exposed to otherness. Her contribution to follow-up and synthesize the scientific works of inter-war Lithuanian educators places a high value on her scientific achievements. M. Lukšienė’s foresight of the Lithuanian education strategy – to maintain the Lithuanian identity through its culture – describes the duality of her ideas that make the core of intercultural education: to develop dynamic and modern Lithuanians tolerant and open to otherness, while, on the other hand, bearing and respecting their own cultural background. The analysis of the empirical survey related to teachers’ intercultural education will be published in the next issue of the journal.